LOCAL FLAPS AND FULL-THICKNESS SKIN GRAFTS FOR MEDIAL CANTHAL REGION RECONSTRUCTION: A CLINICAL EXPERIENCE - Stevkovska, Mare; Marcikikj, Greta; Oranska, Gordana; Rajkovska Kimovska, Ana; Damovska, Elena; Majher Tomic, Vesna; Gruev, Vladislav (Journal of Morphological Sciences, 2025)
Introduction: The medial canthal region, above the medial canthal tendon, is where the upper and lower eyelids, eyebrows, and nose converge. Its skin varies in color, texture, and thickness, remaining thin, supple, and concave around the periorbital area. These anatomical complexities pose challenges for reconstruction after skin cancer excision. Aim: This paper presents our five-year experience in reconstructing medial canthal defects using glabellar and nasal flaps, as well as full-thickness skin grafts (FTSG). Material and methods: At our hospital, 32 patients underwent medial canthal reconstruction using a single flap: glabellar flap (85%), rhomboid flap (9%), or full-thickness skin graft (FTSG) (6%). Satisfactory outcomes were achieved, including favorable pathology findings (mostly basal cell carcinoma), no recurrence, and good aesthetic results. Conclusion: Our findings highlight a clear preference for local flaps as the first choice in medial canthal reconstruction. As a one-stage procedure, they achieved satisfactory aesthetic results, with both the reconstructed and donor sites becoming acceptable to patients over time. When patient health or defect size posed limitations, full-thickness skin grafts (FTSG) served as a viable alternative. Key words: medial cantal region, local flaps, glabellar flap, Limberg flap, FTSG